Mother’s Knowledge and Child Nutritional Status Relationship - Rizqi Nursasmita; Fenisya Febrilia; Intan Asri Nurani (Rajaki of Tulip Medika Publisher, 2024)
Background: Children are a group that has a high risk of their nutrition. Improper breastfeeding and lack of knowledge about nutrition or ability to apply information in daily life, especially mother’s knowledge, can increase mortality much higher. Eating patterns, birth weight and economic status are not related to the incidence of malnutrition. This proves that the mother's role is very important in her child's growth and development which can affect nutritional status. Purpose: To determine the relationship between mother’s knowledge and child nutritional status in Makasar Community Health Center, East Jakarta, Indonesia. Method: This study used cross sectional design. The research sample consisted of 30 respondents. The sampling techniqueuses purposive sampling. The research instrument is mother’s knowledge about child nutrition. Data analysis used the chi-square test to determine the relationship between variables. Results: It was found that 3.3% of child experienced malnutrition with a low level of mother’s knowledge and 50% child experience good nutrition with a good level of mother’s knowledge. The results of the study obtained a p value of 0.001 <0.05 which indicates that there is a relationship. Conclusion: There is a relationship between mother’s knowledge and child nutritional status in Makasar Community Health Care.